Academic Resilience During the COVID-19 Pandemic: A Triarchic Analysis of Education Policy Developments across Canada - Volante, Louis; Lara, Camila; Klinger, Don A.; Siegel, Melissa (Canadian Journal of Education / Revue canadienne de l'éducation, 2022)
This study employed a qualitative content analysis of provincial policy documents, following deductive methods, to examine academic resilience and education policy developments across Canada during the COVID-19 pandemic. More specifically, the study explicates the nature and scope of provincial policy responses to the global pandemic that address academic issues, physical health and well-being, and mental health issues for K–12 students. The pan-Canadian analysis revealed a total of 62 documents were issued between January 2020 and December 2021 that addressed one or more of the triarchic dimensions of academic resilience. The findings suggested greater attention was devoted to academic issues and there was a general lack of policy differentiation in terms of how specific resources and supports were to be directed within provincial educational jurisdictions.